The Validity and Practicality of Augmented Reality-Based Media Development on Science Matter - Siahaan, Sardianto Markos; Patriot, Evelina Astra; Scristia, Scristia; Helen, Helen; Kalsum, Umi; Putri, Regita Elsa (Jurnal Pendidikan MIPA, 2023)
Abstract: Augmented reality is a learning media developed massively and utilized by educators to visualize abstract science concepts into concrete concepts. This study aims to analyze the validity and practicality of augmented reality-based media development on science matter to enhance science conceptual learning. This research is development research conducted to design products of learning media based augmented reality. The development model used is the Alessi and Trollip development model, which concentrates on augmented reality media development. The stage in this research, namely, planning stage, design stage and development stage. The data analysis technique used a questionnaire instrument and the technical descriptive statistical analysis. The results of this study are: the development of augmented reality-based learning media on water cycle and earth rotation material in the form of consisting of competencies and indicators, picture, sound, materials, and mini test; validity assessment by material experts with an average score of 94.44% in the "very valid" category, the validity assessment by learning media design experts with an average score of 95.83% in the "very valid" category; and the validity assessment by language experts with an average score of 80% in the "valid" category. The other results 95% of teacher responded positively to the questionnaire in the "practice" category. The results of this study indicate that augmented reality-based learning media can be categorized as valid and practice learning media. Keywords: augmented reality, learning media, practicality, validity. Abstrak: Augmented reality menjadi salahsatu media pembelajaran yang telah dikembangkan secara massif dan dimanfaatkan oleh pendidik untuk memvisualisasikan konsep IPA yang abstrak menjadi konsep yang konkret. Penelitian ini bertujuan untuk menganalisis validitas media pembelajaran berbasis augmented reality pada materi siklus air dan rotasi bumi. Metode penelitian yang digunakan adalah model pengembangan dan penelitian oleh Allesi dan Trollip, yang berfokus pada pengembangan media pembelajaran. Data dikumpulkan menggunakan lembar validasi berupa kuesioner dan dianalisis menggunakan statistic. Adapun tahapan dari model pengembangan yang digunakan adalah tahap perencanaan, tahap desain dan tahap pengembangan. Dari hasil penelitian didapatkan bahwa pengembangan media pembelajaran berbasis augmented reality pada materi siklus air dan rotasi bumi terdiri dari kompetensi dasar dan indikator, gambar, suara, materi dan juga kuis, Validasi oleh ahli materi menghasilkan persentase sebesar 94.44% sengan kategori sangat valid, hasil persentase validitas oleh ahli media sebesar 95.83% dengan kategori sangat valid dan validasi oleh ahli bahasa dengan persentase 80% pada kategori valid. Hasil yang lain menunjukkan respon guru sebesar menunjukkan hasil kategori "praktis" category. Hasil ini menunjukkan bahwa media pembelajaran berbasis augmented reality dapat dikategorikan media yang valid dan praktis.  Kata kunci: augmented reality, media pembelajaran, praktis, validitas. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp717-729